MUTU BAWANG GORENG DARI BAWANG MERAH LEMBAH PALU - Anisa, Nur; Rahmatu, Rostiati; Kadir, Syahraini (AGROTEKBIS, 2013)
Local varieties onions (Allium ascolinicum L) of Palu are mostly presented as fried onion, it because has excellent taste that demanded by consumers. This study was planned to determine the quality of the chemical and physical properties, as well the organoleptic of the fried onions which were produced from various locations in Palu valley. Research design was a randomized block design with 5 locations of onion planting as treatments and defined 4 plots of anion in each village as group. The 5 locations namely are Bolupontu jaya, Soulowe, Guntarano, Maku and Oluboju. Data were analyzed by analysis of variance and tested with Honestly Significant Difference (HSD) method. The results indicated that the location where the onions were planted in Palu valley affected significantly the chemical properties such as water content, free fatty acid levels, oil content, carbohydrate content, protein content, and mineral content especially calcium and sulfur. Further, the location was also significantly effect on dry biomass of fried onions.